Pediatric Deep Neck Space Infections: A Medical and Surgical Perspective - Mohandas, Sindhu; Gregory, Stacie; Chun, Robert H.; Huppler, Anna R. (Journal of Pediatric Infectious Diseases, 2019)
Pediatric deep neck space infections (DNSI) are common in children. If unrecognized, DNSIs can rapidly progress with the potential for developing serious complications. Children fair better than their adult counterparts in the face of complications such as mediastinitis, but early recognition and aggressive management is key to prevent mortality and limit morbidity. Knowledge of the anatomy related to the deep neck spaces helps in anticipating and managing the potential complications. In this article, we review the clinical presentation, complications, and management in pediatric DNSI from the point of view of the pediatric infectious disease physician and the otolaryngologist. We discuss the best management based on current available evidence and the experience of the authors.
Keywords: deep neck space; neck abscess; retropharyngeal; parapharyngeal; peritonsillar; mediastinitis.